Anatomic factors as contributing risk factors in implant therapy. Issue 1 (12th August 2019) - Ramanauskaite, Ausra; Becker, Jürgen; Sader, Robert; Schwarz, Frank
Abstract: Damage to the critical anatomic structures during dental implant placement can lead to serious complications, including intra‐ or postoperative bleeding, hematoma formation, or varying degrees of neurosensory alteration. These complications usually occur when the anatomic features of the major blood vessels and their anastomoses, neurovascular bundles, and alveolar ridge contour are not properly investigated prior to the surgery. Therefore, having proper knowledge of specific anatomic factors is key to avoiding intra‐ and postsurgical complications. The aim of the current review is to summarize the anatomic structures and their variations in the mandible and maxilla as contributing risk factors in implant therapy.